The impact of government health and education expenditure on income inequality in EU - Ionuț Jianu (International Finance and Banking Conference FI BA 2018, XVIth Edition, Theoretical and Applied Economics. Special Issue, 2018)
This research aims to provide an overview of the existing inequalities and their drivers in the member states of the European Union as well as their developements in the 2002-2008 and 2009- 2015 sub-periods. It also analyses the impact of health and education government spending on income inequality in the European Union over the 2002-2015 period. In this context, I applied the Estimated Generalized Least Squares method using panel data for the 28-member states of the European Union.
Keywords: D63; I14; I24; 330; inequality; income; education; health; unemployment